The effect of conformity on aggression behaviour moderated by the intensity of online game playing in late adolescence in Bandung - Mochammad Azmi Hindriadi Fakhrizal, - (2021)
This study aims to find out the effect of conformity on aggressive behaviour moderated by the intensity of online game playing in late adolescents in Bandung. There are 400 participants aged 18 - 22 years old, male and female, domiciled in Bandung, and playing online game for 1 - 3 hours a day. The research instruments was an adaption of the conformity theory of Sears, et al. (1991), aggression questionnare scale (AQS) developed by Buss & Perry (1992), and the intensity of playing online game adapted from the theory of Chaplin (2004). The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that conformity can affect aggression behaviour with 1% contribution and 0.044 < (0.05) significance, it also has a significant influence on the intensity of online game playing by 1.3% and 0.022 < (0, 05) significance value. The intensity of online game playing can moderate conformity effect on aggression behaviour in social environment where there is an increase in the r^2 value from 0.022 to 0.038. These results indicate that the intensity of playing online game as a moderating variable can reinforce the influence of social conformity on aggression behaviour in late adolescents in Bandung. The higher intensity of online game, the stronger social conformity influence on aggression behaviour. Keywords: aggression behaviour; conformity; intensity of online game playing; late adolescence.